Clinical trials in low and middle-income countries - Successes and challenges - Surbhi Grover; Melody Xu; Anuja Jhingran; Umesh Mahantshetty; Linus Chuang; William Small, Jr; David Gaffney (Elsevier, 2017)
Gynecologic malignancies affect women in low and middle-income countries (LMICs) at equal or higher rates compared to high income countries (HICs), yet practice guidelines based on clinical trials performed in HICs do not routinely account for resource disparities between these regions. There is a need and growing interest for executing clinical trials in LMICs. This has led to the creation of multinational cooperative groups and the initiation of several ongoing clinical trials in Mexico, China, and Korea. In this article we describe the challenges involved in initiating clinical trials in LMICs, review current efforts within surgical, medical, and radiation oncology, and introduce high priority topics for future research.